Glymphatic system in the thalamus, secondary degeneration area was severely impaired at 2nd week after transient occlusion of the middle cerebral artery in rats - Li, Chanchan; Lin, Luyi; Sun, Chengfeng; Hao, Xiaozhu; Yin, Lekang; Zhang, Xiaoxue; Tian, Jiaqi; Yao, Zhengwei; Feng, Xiaoyuan; Yang, Yanmei (Frontiers in Neuroscience, 2022)
Background and Objectives: The glymphatic system is a recently discovered cerebrospinal fluid transport system and little is known about its dynamic changes after stroke. This study aimed to dynamically observe the structural and functional changes of the impaired glymphatic system in the thalamus after ischemic stroke by pathology and MRI. Materials and Methods: Ischemic stroke was induced by the middle cerebral artery occlusion (MCAO) model. A total of 20 Sprague-Dawley rats were randomly assigned into four groups: sham, MCAO 1week, MCAO 2week, and MCAO 2month. All rats successively underwent neurological examination, dynamic contrast-enhanced MRI (DCE-MRI), and immunofluorescence staining. Immunofluorescence staining of glial fibrillary acidic protein (GFAP), aquaporin-4 (AQP4), ionized calcium-binding adaptor molecule 1 (Iba1), and beta-amyloid precursor protein (APP) were done in thalamus ventroposterior nucleus. Results: The astrocyte and microglial activation and the APP deposition in the MCAO 2week group were the highest (P<0.05 for all). The AQP4 polarization rates of the MCAO 2week and 2month groups were the lowest (P<0.05 for all). Although there was no correlation between histological changes and MRI metrics in all 4 groups (P＞0.05 for all), the tendency of the APP deposition was nearly consistent with the one of the contrast agent retention in DCE-MRI. Conclusions: The glymphatic system in the thalamus was severely impaired at 2nd week after MCAO, and may be revealed by DCE-MRI. This study may provide a relevant theoretical basis for making a thorough inquiry of the mechanism of brain injury after stroke and clinical treatment of ischemic stroke and help readers appreciate the importance of DCE-MRI.